Software testing : testing across the entire software development life cycle / Gerald D Everett, Raymond McLeod - Everett, Gerald D
Software Testing presents one of the first comprehensive guides to testing activities, ranging from test planning through test completion for every phase of software under development,160;and software under revision. 160;Real life case studies are provided to enhance understanding as well as a companion website with tools and examples.